The occurrence of occupational health hazards in districts health facilities in Kigali, Rwanda - Nwankwo, Chinenye Mercy; Karanja, Simon; Vasanthakaalam, Hilda (International Journal Of Community Medicine And Public Health, 2017)
Background: Health workers are constantly exposed to chemical, physical, psychological and biological agents that affect their health. Regular information is critical for setting priorities necessary to enhance workers health and safety. The study determined the occurrence of occupational health hazards among health care worker in the three selected district health facilities in Kigali, Rwanda (July-December 2016). Methods: It adopted a cross-sectional design involving both qualitative and quantitative data collection approaches. A total of 249 healthcare workers were selected systematically for interviewing. Data were collected using semi structured questionnaires, a focus group discussion guide and an observational checklist. Data analysis involves descriptive and inferential statistics. The observed differences in the parameter of estimate were considered significantly different at p<0.05. Results: Back-ache and accidents experienced while working contributed majority of occupational hazards, thus; 151 (60.6%, 95% CI=54.28–66.75) and 139 (55.8%, 95% CI=49.42–62.09), respectively. Health hazards from violence and molestation contributed 8 (3.2%, 95% CI=01.39–6.23) of the cases, furthermore, lack of hospital management commitment to policy, poor policy enforcement, health facility safety activities, employees’ participation in safety programs and post exposure compliance were associated with occurrence occupational hazard among healthcare workers (p<0.05). Qualitatively, the process of waste collection, sorting, marking, storage and transportation were not in line with policy regulations and contributed further to the hazard cases. Conclusions: Finally, direct job supervision, proper job placement, training and effective safety communication and reporting can enhance work safety and risk aversion.